2019
DOI: 10.1177/1203475419861078
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric SJS/TEN Subdued by a Combination of Dexamethasone, Cyclosporine, and Etanercept

Abstract: We report a case of an 17-year-old male with a drug reaction in the spectrum of Stevens-Johnson syndrome (SJS)/toxic epidermal necrolysis (TEN), triggered by carbamazepine, who was succesfully treated with the combination of dexamethasone, cyclosporine, and etanercept. This triple therapy halted and prevented skin epidermolysis without immediate or late onset complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 12 publications
0
14
0
1
Order By: Relevance
“…As a result, there is no established standard of care pertaining to pharmacologic treatment. Due to the immunologic nature of the disease, it is believed that immunosuppressive therapies will aid in treatment, and many case reports have reported positive results with varying treatment regimens involving different combinations of corticosteroids, IVIg, cyclosporine, and TNF-alpha inhibitors [ 21 , 78 , 79 , 80 , 81 ]. However, it is difficult to determine if disease remission was due to specific treatment or simply the natural history of the disease.…”
Section: Clinical Updatesmentioning
confidence: 99%
“…As a result, there is no established standard of care pertaining to pharmacologic treatment. Due to the immunologic nature of the disease, it is believed that immunosuppressive therapies will aid in treatment, and many case reports have reported positive results with varying treatment regimens involving different combinations of corticosteroids, IVIg, cyclosporine, and TNF-alpha inhibitors [ 21 , 78 , 79 , 80 , 81 ]. However, it is difficult to determine if disease remission was due to specific treatment or simply the natural history of the disease.…”
Section: Clinical Updatesmentioning
confidence: 99%
“…Excitingly, TNF-α antagonists are translated into clinical therapeutics for SJS/TEN in recent years. Tons of evidence supports TNF antagonists halt SJS/TEN (Paradisi et al, 2014;Gavigan et al, 2018;Shear et al, 2018;Trujillo-Trujillo et al, 2018;Chafranska et al, 2019;Coulombe et al, 2019;Pham et al, 2019;Zhang et al, 2020). A randomized controlled trial compared etanercept (a TNF inhibitor) with systemic corticosteroid treatment in adult SJS/TEN patients and showed a decreased SCORTEN-predicted mortality rate, reduced skin healing time, and less gastrointestinal hemorrhage in the etanercept group.…”
Section: Tnf-α-related Apoptosismentioning
confidence: 99%
“…51 Reports of etanercept efficacy in paediatric medication-induced SJS and TEN suggest promise. [73][74][75] A recent meta-analysis in the respiratory literature showed that serum TNF-a levels are elevated in MP pneumonia. 76 This suggests that it is possible we may see a dichotomous response to anti-TNF agents in RIME caused by bacteria such as MP or C. pneumoniae compared with RIME caused by viruses such as influenza B.…”
Section: Treatmentmentioning
confidence: 99%
“…Infliximab was effective in one case that was also treated with meropenem 51 . Reports of etanercept efficacy in paediatric medication‐induced SJS and TEN suggest promise 73‐75 . A recent meta‐analysis in the respiratory literature showed that serum TNF‐α levels are elevated in MP pneumonia 76 .…”
Section: Treatmentmentioning
confidence: 99%
See 1 more Smart Citation